Between-group competition enhances cooperation in resource appropriation games (2019)
Cooperation in public goods games increases in the presence of between-group competition. In this study, we validate the effect of between-group competition in a different social dilemma, a resource appropriation game. Unlike the voluntary contributions setting, group performance in this game increases with the exercise of a passive choice: not appropriating units in an open-access resource. We conducted an incentivized experiment using 276 undergraduate students in which groups of four subjects played a resource appropriation game. Different groups within a session were ranked in each round according to the group's aggregate payoff. This ranking determined a group performance multiplier, which increased the payoffs in groups ranked above the median and decreased the payoffs in groups below the median. The multipliers were small enough to keep the individual benefits from appropriation larger than the individual benefits from a higher payoff multiplier (derived from an improvement in group ranking by not appropriating the resource unit). We found that implementing this small group performance multiplier decreased the average appropriation by 31%. This efficiency-enhancing device generated a 19-percentage-point increase in overall earnings in a given session. © 2018 Elsevier B.V.